Foreign entrant survival and foreign market share: Canadian companies' experience in united states medical sector markets - Mitchell, Will; Shaver, J. Myles; Yeung, Bernard (Strategic Management Journal, 1994)
Abstract We show that successful foreign market entry is related to the extent of foreign presence in an industry at the time of entry. Survival of 31 Canadian‐based businesses that entered 24 U.S. medical sector markets between 1968 and 1989 tended to be somewhat longer in product markets in which foreign‐based businesses held a moderate market share when the Canadian businesses entered than in low and high foreign share product markets. The result controls several other industry and business‐level factors, including industry concentration, entry year, corporate size, related diversification, entry mode, and service sector status.